KONTRIBUSI HIPERTENSI, DIABETES MELLITUS, DAN HIPERCHOLESTEROLEMIA TERHADAP KEJADIAN STROKE ISKEMIK PADA ORANG DEWASA - Heltty, Heltty; Krismiadi, Dedi; Masriwati, Siti; Yati, Mimi; Nofitasari, Ari (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Stroke is a cerebrovascular disease caused by blockage or rupture of blood vessels in certain parts of the brain. Various factors can cause ischemic stroke. This study aims to determine the contribution of hypertension, diabetes mellitus, and hypercholesterolemia to the incidence of stroke. This type of study uses a Case-Control design. The respondents of this study were 152 respondents, sampling using a purposive sampling technique. Respondents of patients with conditions suspected of having a stroke based on the symptoms that appear who treated at the Kendari City Hospital. Data collection used measuring instruments (tension meter and easy touch). Data analysis was carried out using univariate and bivariate analysis tests. The results showed that hypertension, diabetes mellitus, and hypercholesterolemia were risk factors for stroke with an estimated value of hypertension = 3.986, diabetes mellitus = 0.289, and hypercholesterolemia = 1.699. Recommendation: Hypertension, diabetes mellitus, and hypercholesterolemia are risk factors for stroke, so it is very important for nurses to provide education to the community so that they can control blood pressure, blood glucose levels, and cholesterol to prevent stroke.